Girls in trades: tokenism and sexual harassment inside the VET classroom - Bridges, Donna [Verfasser]; Wulff, Elizabeth [Verfasser]; Krivokapic-Skoko, Branka [Verfasser]; Bamberry, Larissa [Verfasser] (My University, 2024)
„When women enter occupations that have historically and traditionally been the realm of men, they face a multitude of barriers that make their experience difficult and that contribute to a gender-segregated workforce. Vocational Education and Training (VET) is the entryway to employment in the skilled trades, and VET providers have a role in introducing students to the industry, in the formation of occupational identity and occupational behaviours, establishing workplace cultures and standards of professionalism. Furthermore, VET has a moral and legal obligation to provide a safe classroom for all students. This paper reflects on the role of VET in perpetuating gender segregation in the skilled trades in Australia. We report on a qualitative research project with tradeswomen, apprentices, industry and government representatives that found that significant barriers confront tradeswomen apprentices in VET institutions. The study found that VET has the capacity to normalise the tokenism of women and contribute to gender harassment. We argue that a VET classroom environment where gender inequalities and harassment are normalised, and a gender biased apprenticeship system, contribute to gender segregation in the skilled trades.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; P 1.3 Frauen; G 2.4.5 Gender Mainstreaming; 370; Berufsausbildung; Handwerk; Männerberuf; Frauen; Geschlechterrolle; Geschlechtersegregation; Australien